2019
DOI: 10.15419/bmrat.v6i11.577
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and survival of patients with hepatocellular carcinoma at a cancer treatment facility

Abstract: Background: Hepatocellular carcinoma (HCC) is the third leading cause of cancer-related deaths. This study aimed to determine the survival of patients with HCC at our treatment facility. Methods: We retrospectively studied 278 patients with HCC who were seen between 2007 and 2013. Of these patients, 84.4% had evidence of prior infection with hepatitis C, while 7.8% had markers of hepatitis B infection. Results: Median survival was 24.6 months for transarterial chemoembolization (TACE), 61 months for ablative t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Although a great effort was made, most developing Asian countries with low human development index are still faced with great problems in the treatment of HCC. In Pakistan, the percentage of patients receiving supportive care declines from 86.0% 110 in 2004 to 15.2% 111 in 2013 and most HCC cases receive trans‐arterial chemoembolization (TACE). The median survival time rises from 10.5 months to 23.9 months, which is a remarkable progress.…”
Section: Prevention and Surveillancementioning
confidence: 99%
“…Although a great effort was made, most developing Asian countries with low human development index are still faced with great problems in the treatment of HCC. In Pakistan, the percentage of patients receiving supportive care declines from 86.0% 110 in 2004 to 15.2% 111 in 2013 and most HCC cases receive trans‐arterial chemoembolization (TACE). The median survival time rises from 10.5 months to 23.9 months, which is a remarkable progress.…”
Section: Prevention and Surveillancementioning
confidence: 99%
“…In the study of Choudhry, A et al 14 reported that the child Pugh class B was most common in 40.2% of the cases, followed by class A 39.2% and class 20.6%. Inconsistently, Mansoor H et al 15 reported that the most of the patients 84%, had child Pugh class A, followed by 11.5% of cases having child Pugh class B, and 4.3% having child Pugh class C.…”
Section: Discussionmentioning
confidence: 96%
“…Even in segmental portal vein thrombosis, resection can be offered. 30 Regarding liver transplantation, most countries in Asia follow the Milan criteria, whereas China and Hong Kong follow the University of California San Francisco criteria. 31 With the shortage of deceased donors, most Asian countries use living-donor transplantation.…”
Section: Management Of Hcc In Asian Settingmentioning
confidence: 99%
“…Most Asian guidelines recommend surgical resection in patients with preserved liver function for solitary lesions or multiple lesions that are localized. Even in segmental portal vein thrombosis, resection can be offered 30 …”
Section: Management Of Hcc In Asian Settingmentioning
confidence: 99%